Comparative safety of multiple doses of erythropoietin for the treatment of traumatic brain injury: A systematic review and network meta-analysis - Zheng, Qingyong; Duan, Dan; Xu, Jianguo; Wang, Xing; Ge, Yonggui; Xiong, Lu; Yang, Jingjing; Wulayin, Saimire; Luo, Xiaofeng (Frontiers in Neurology, 2022)
Introduction Over the past few decades, advances in traumatic brain injury (TBI) pathology research have dynamically enriched our knowledge. Therefore, we aimed to systematically elucidate the safety and efficacy of erythropoietin (EPO) dosing regimens in patients with TBI. Methods Data search included PubMed, the Cochrane Library, Embase, Web of Science, and ClinicalTrials.gov for related research published before July 2022. The network meta-analysis was conducted using ADDIS 1.16.8, and the CINeMA tool was used to assess the quality level of evidence. Results A total of six RCTs involving 981 patients were included in the network meta-analysis. EPO did not significantly reduce mortality in patients with TBI, but its risk of death decreased with increasing dosage (odds ratio (OR) of 12,000u vs. placebo = 0.98, 95% CI: 0.03–40.34; OR of group 30,000u vs. placebo = 0.56, 95% CI: 0.06–5.88; OR of 40,000u vs. placebo = 0.35, 95% CI: 0.01–9.43; OR of 70,000u vs. placebo = 0.29, 95% CI: 0.01–9.26; OR of group 80,000u vs. placebo = 0.22, 95% CI: 0.00–7.45). A total of three studies involving 739 patients showed that EPO did not increase the incidence of deep vein thrombosis in patients with TBI. However, the risk tended to rise as the dosage increased. Another two studies demonstrated that EPO did not increase the incidence of pulmonary embolism. The quality of evidence for all outcomes was low to moderate. Conclusion Although the efficacy of EPO was not statistically demonstrated, we found a trend toward an association between EPO dosage and reduced mortality and increased embolic events in patients with TBI. More high-quality original studies should be conducted to obtain strong evidence on the optimal dosage of EPO. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=272500. The study protocol was registered with PROSPERO (CRD42021272500).